Artificial optimization of bamboo Ppmar2 transposase and host factors effects on Ppmar2 transposition in yeast - Zhou, Xiaohong; Xie, Jiamin; Xu, Chao; Cao, Xiuling; Zou, Long-Hai; Zhou, Mingbing (Frontiers in Plant Science, 2022)
Mariner-like elements (MLEs) are promising tools for gene cloning, gene expression, and gene tagging. We have characterized two MLE transposons from moso bamboo, Ppmar1 and Ppmar2. Ppmar2, is smaller in size and has higher natural activities, thus making it a more potential genomic tool compared to Ppmar1. Using a two-component system consisting of a transposase expression cassette and a non-autonomous transposon cotransformed in yeast, we investigated the transposition activity of Ppmar2 and created hyperactive transposases. Five out of 19 amino acid mutations in Ppmar2 outperformed the wild-type in terms of catalytic activities, especially with the S347R mutant having 6.7-fold higher transposition activity. Moreover, 36 yeast mutants with single-gene deletion were chosen to screen the effects of the host factors on Ppmar2NA transposition. Compared to the control strain (his3Δ), the mobility of Ppmar2 was greatly increased in 9 mutants and dramatically decreased in 7 mutants. The transposition ability in the efm1Δ mutant was 15-fold higher than in the control, while it was lowered to 1/66 in the rtt10Δ mutant. Transcriptomic analysis exhibited that EFM1 defection led to the significantly impaired DDR2, HSP70 expression and dramatically boosted JEN1 expression, whereas RTT10 defection resulted in significantly suppressed expression of UTP20, RPA190 and RRP5. Protein methylation, chromatin and RNA transcription may affect the Ppmar2NA transposition efficiency in yeast. Overall, the findings provided evidence for transposition regulation and offered an alternative genomic tool for moso bamboo and other plants.